Sodium orthovanadate inhibits growth of acute leukemia HL60 cells and HL60/A cells in vitro. Issue 9 (28th September 2020) - Zhang, Lulu; Wei, Nan; Guan, Guoying; Song, Tao; Xu, Yingying; Wang, Shuye; Zhou, Jin
Abstract: Vanadium is an ultratrace element. The transition metal vanadium, widely exists in the environment and exhibits various biological and physiological effects in the human body, yet with no presently known specific physiological function in mammals. Sodium orthovanadate (SOV) is a kind of vanadium compound. SOV has shown promising antineoplastic activity in several human cancers. But the effects of SOV on acute promyelocytic leukemia (APL) are still unknown. In the present study, for the first time, we found that SOV could inhibit proliferation, induce G2 /M cell cycle arrest and apoptosis, and could inhibit autophagy of acute leukemia cell lines in vitro . Thus, our findings suggest that SOV could effectively suppress the growth of acute leukemia HL60 cells and HL60/A cells through the regulations of proliferation, cell cycle, apoptosis and autophagy, and thus may act as a potential therapeutic agent in APL treatment.